2020
DOI: 10.1002/slct.202003415
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Treated Cu Foam Catalyst for Selective Electrochemical CO2 Reduction Reaction

Abstract: The electrochemical reduction of CO 2 is a promising route to convert waste products to valuable chemicals. Search for suitable and efficient CO 2 reduction electrocatalysts with high C 2 :C 1 selectivity holds great promise. Herein, for the first time we have developed a molten salt oxidized method to modify the morphology and oxidation state of a Cu-foam catalyst. The catalyst displayed a current density of 30 mA cm À 2 (À 1.4 V versus reversible hydrogen electrode) and an ethylene/ methane ratio of 870. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This peak decrease can be related to the Sn 4+ reduction and/or its leaching into the solution. The SEM images showed that the morphology of microsized SnO 2 did not change during the CO 2 RR; however, it could be verified that the SnO 2 particles became less agglomerated and more uniformly dispersed on the carbon fibers, which could relate to the surface reconstruction during CO 2 RR operation, as observed in other studies [41][42][43]. Therefore, the enhanced CO 2 RR performance after the first cycle could also be related to the better distribution of the SnO 2 particles across the carbon fiber surface.…”
Section: Resultssupporting
confidence: 67%
“…This peak decrease can be related to the Sn 4+ reduction and/or its leaching into the solution. The SEM images showed that the morphology of microsized SnO 2 did not change during the CO 2 RR; however, it could be verified that the SnO 2 particles became less agglomerated and more uniformly dispersed on the carbon fibers, which could relate to the surface reconstruction during CO 2 RR operation, as observed in other studies [41][42][43]. Therefore, the enhanced CO 2 RR performance after the first cycle could also be related to the better distribution of the SnO 2 particles across the carbon fiber surface.…”
Section: Resultssupporting
confidence: 67%
“…The molten salt process, in which a molten nitrate functions both as a high‐temperature oxidizing agent and reaction medium, was developed by Wang's group to modify the morphology and oxidation state of a Cu‐foam catalyst (Figure 6e) [73] . The catalyst's surface was enriched with Cu I and Cu 0 sites as verified by the in situ soft XAS measurements.…”
Section: Engineering the Surface Microenvironment Of Catalystsmentioning
confidence: 89%
“…[72], Copyright 2020 American Chemical Society, Ref. [73], Copyright 2020 Wiley‐VCH, and Ref. [74], Copyright 2016 American Chemical Society.…”
Section: Engineering the Surface Microenvironment Of Catalystsmentioning
confidence: 99%
“… The surface activation of CO 2 RR electrode achieved by executing different treatments, including a–c) gas plasma treatment, [71a–c] d) mass transport control, [72] e) molten salt process, [73] and f) hydrazine treatment [74] . Adapted, with permission, from: Ref.…”
Section: Engineering the Surface Microenvironment Of Catalystsmentioning
confidence: 99%
“…[72], Copyright 2020 American Chemical Society, Ref. [73], Copyright 2020 Wiley‐VCH, and Ref. [74], Copyright 2016 American Chemical Society.…”
Section: Engineering the Surface Microenvironment Of Catalystsmentioning
confidence: 99%